SAT0238 An Exploratory Clinical and Imaging Study Evaluating Abatacept in the Management of Poor Prognosis ACPA Negative Undifferentiated Arthritis. (10th June 2014) - Buch, M.H.; Rakieh, C.; Hensor, E.; Middleton, E.; Horton, S.; Das, S.; Pickles, D.; Ward, J.; Fechtenbaum, M.; Tan, A.L.; Wakefield, R.; Freeston, J.; et al.
Abstract : Background: A preliminary study on ACPA positive UA suggested abatacept might delay its progression to RA 1 . No therapy has been shown to be effective in ACPA negative patients. Ultrasound (US) Power Doppler (PD) is a powerful predictive factor of persistent inflammatory arthritis in ACPA negative pts 2 . Objectives: To evaluate Abatacept's effect in poor prognosis ACPA negative pts and impact on US PD. Methods: In this pilot, open-label, prospective study, patients with ACPA negative UA (≥2 joint synovitis) and PD ≥1 were recruited. Additional key inclusion criteria: symptom duration ≥3/≤18 months, DMARD-naive. All patients received 12 months abatacept monotherapy. Primary endpoint is proportion of patients in DAS44 remission at 6 months. Clinical assessments and US [Grey Scale (GS)/PD] as objective measures of outcome were undertaken at baseline, 6, 12, 18, 24 months. 20 joints scanned, each assigned GS and PD score (max of 3), gives max totals scores of 60 for each. All patients have reached 24 month follow-up; we present a follow-up 3 complete 12 month descriptive analysis. Results: 20/23 pts were screened and enrolled [14 female, 6 male; mean (SD) age 53.2 (11.1) yrs, symptom duration 7.5 (0.9) months]. 1 patient, erroneously included having seroconverted to ACPA from screening to baseline has been excluded from the analysis. 9 patients satisfied 2010 RA classification criteria. At 6 months, 32% achieved DAS44rem and 32& DAS28 rem; increased to 44% and 56% respectively by 12 months. Mean (SD) DAS44/DAS28 reduction was observed at 6 and 12 months (Table 1 ). Baseline median (IQR) CRP of 9 (0-23) normalized to 0 (0-16) by 3 months, maintained to 12 months, 0 (0-6); median (IQR) ESR (mm/hr) reduced from baseline of 16 (6-28) to 8 (6-12) and 7 (3-12) at 6 and 12 months respectively. Median GS and PD also decreased (Table 1 ). Median (range) total number of joints scoring PD >0 reduced from 6 (1-28) at baseline to 2 (0-20) and 2 (0-13) at 6 and 12 months respectively. The joints with highest proportion of patients showing baseline PD >0 were the wrist (70%) and MCP joints (80%); this remained unchanged in the wrist following 12 months abatacept, with a 50% reduction in percentage patients showing PD >0 in the MCP and PIP joints (table 1). Conclusions: This pilot study demonstrates patients with poor prognosis ACPA negative UA/RA have marked inflammatory disease and suggests abatacept monotherapy confers clinical improvement; with half in remission by 12 months and notable reduction in PD signal. PD reduction seemed most amenable to change in the MCP and PIP joints. Ongoing analysis on subsequent follow-up of this cohort will provide an indication of the durability of this effect. References: Emery P, et al. Ann Rheum Dis 2010; 69(3). Freeston J, et al. Ann Rheum Dis 2010; 69(2). Buch MH, et al. EULAR 2012. Acknowledgements: This study received drug and financial support from Bristol Myers Squibb Disclosure of Interest: M. Buch Grant/research support: Bristol Myers Squibb, Pfizer Ltd, Consultant for: Abbvie, Bristol Myers Squibb, Chugai, Roche, Pfizer Ltd, C. Rakieh: None declared, E. Hensor: None declared, E. Middleton: None declared, S. Horton: None declared, S. Das: None declared, D. Pickles: None declared, J. Ward: None declared, M. Fechtenbaum: None declared, A. L. Tan: None declared, R. Wakefield: None declared, J. Freeston: None declared, P. Emery Grant/research support: Abbvie, Consultant for: Abbvie, Bristol Myers Squibb, Chugai, MSD, Roche, Pfizer Ltd DOI: 10.1136/annrheumdis-2014-eular.3397